2022
DOI: 10.29219/fnr.v66.8469
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin alleviates kidney injury in rats via PI3K/AKT pathway by enhancing MAP4 expression

Abstract: Background: Troxerutin is a flavonoid compound and possesses potential anti-cancer, antioxidant, and anti-inflammatory activities. Besides, cisplatin is one of the most widely used therapeutic agents, but the clinical uses of cisplatin are often associated with multiple side effects, among which nephrotoxicity is more common. Objective and design: This study explored the protective effects of troxerutin (150 mg kg−1 day−1 for 14 days) against cisplatin-induced kidney injury and the potential mechanism us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The present finding reveals that troxerutin treated group in combination with nicotine decreased the levels of IL-10 and increased the IL-1β expression. Tong Xu Guan 21 reported that, troxerutin not only decreased the levels of TNF-α, NF-κB, IL-1β and IL-6 gene expression and but also increased IL-10 level. According to our study, troxerutin significantly increased LPO, MPO in the gill tissue homogenate and decreased enzymatic antioxidant levels (SOD, CAT) and also increased the NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding reveals that troxerutin treated group in combination with nicotine decreased the levels of IL-10 and increased the IL-1β expression. Tong Xu Guan 21 reported that, troxerutin not only decreased the levels of TNF-α, NF-κB, IL-1β and IL-6 gene expression and but also increased IL-10 level. According to our study, troxerutin significantly increased LPO, MPO in the gill tissue homogenate and decreased enzymatic antioxidant levels (SOD, CAT) and also increased the NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Ou et al found that the cAMP/PKA signaling pathway may inhibit the invasion of bladder cancer cells through targeted regulation of MAP4 phosphorylation. [ 29 ] MAP4 is widely involved in PI3K/AKT pathway in kidney injury [ 30 ] as well as in lumbar disc herniation-related diseases. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…[28] Ou et al found that the cAMP/ PKA signaling pathway may inhibit the invasion of bladder cancer cells through targeted regulation of MAP4 phosphorylation. [29] MAP4 is widely involved in PI3K/AKT pathway in kidney injury [30] as well as in lumbar disc herniation-related diseases. [31] YWHAG was mainly involved in the regulation of mitosis and the signal transduction between cells and other biological processes, and was closely related to tumor migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%